(untitled) (Journal of Epidemiology and Public Health, 2021)
Background: The aging process is associated with a greater prevalence of long-term health problems. One of them is a significant increase in problems including mental health problems in the elderly demographic. The World Health Organization (WHO) estimates that about one in every ten elderly people suffer from depress